Software appropriation over time: from adoption to stabilization and beyond - Mendoza, Antonette; Carroll, Jennie; Stern, Linda (Australasian Journal of Information Systems, 2010)
Technologies are introduced into an organization with the aim of improving productivity. However, persistent use of an information system is required to enhance productivity and user satisfaction. In this paper, we examine the process of technology appropriation and the factors that encourage and discourage use of an information system over time. In a longitudinal field study in an educational setting, we identify changing expectations and influences that encourage persistent use of a technology above and beyond adoption. Our work indicates that stabilization of a technology may only be a temporary plateau. Further appropriation may occur beyond initial stabilization as expectations and influences encourage persistent use of a technology. We have found that the driving forces in encouraging productive use of a technology are the ability for users to experience the technology as useful and to have easy access to ongoing training.